Prey choice by Nesticodes rumpes (Araneae, Theridiidae) on Musca domestica (Diptera, Muscidae) and Dermestes ater (Coleoptera, Dermestidae) - Rossi, Marcelo N.; Godoy, Wesley A. C. (Amer Arachnological Soc, 2006)
Nesticodes rufipes is widely distributed in tropical and subtropical regions, being strongly associated with humans. However, few behavioral and ecological studies have investigated interspecific interactions between these spiders and insects of medical and veterinary importance. Here, we have investigated prey choice by N. rufipes when two different prey species, Musca domestica and Dermestes ater, were offered simultaneously. We also quantified the capture of these prey types by this predator in a poultry house and analyzed the association between prey-choice with physical characteristics of the prey. Finally, we discuss whether there is an antagonistic intraguild interaction in such a system composed of N. rufipes (top predator), D. ater (predator of larvae of M. domestica and prey of N. rufipes) and M. domestica (N. rufipes' prey). We found that Musca domestica were more abundant than D. ater in N. rufipes webs in the poultry house. Spiders given a choice of adults of M. domestica plus adults of D. ater, and also on adults plus larvae of M. domestica, preyed more on adult flies than on the other prey types. This preference was probably associated with the lesser mass and shorter lengths of adult flies. Our experiments demonstrated that the predation impact of N. rufipes on D. ater is low when compared to M. domestica. This result provides evidence that an antagonistic interaction between these predators does not occur, suggesting that they are in fact acting either synergistically or additively on M. domestica prey.
Keywords: prey selection; housefly; spider predation; poultry house